A thematic synthesis on the adoption of regression testing techniques in Android projects - Lima, Sara Mendes Oliveira; Campos, Denivan; Machado, Ivan (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
In software testing, employing regression techniques is a viable strategy to deal with the complexity and the constant evolution of applications since its primary goal is to ensure that changes made between versions do not change the system’s behavior. Although the literature has dedicated efforts to developing new regression testing techniques suitable for the Android mobile platform, studies are limited concerning demonstrating which techniques software developers employ in practice. This study aims to report on a thematic synthesis of adopting regression testing techniques in Android projects. The research encompassed four stages: (i) conducting a structured literature review on regression testing techniques for the Android platform, (ii) carrying out an expert survey, (iii) conducting interviews with industry professionals, and (iv) building a thematic synthesis. The thematic synthesis presented a model from analyzing the results obtained in this multimethod study on regression testing techniques. With such a study, we could present empirical evidence on how professionals perform regression testing in Android projects, identify the commonly used regression testing techniques, and leverage the requirements for automating Android applications through regression testing.